5u(8u-1)=0

Simple and best practice solution for 5u(8u-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5u(8u-1)=0 equation:


Simplifying
5u(8u + -1) = 0

Reorder the terms:
5u(-1 + 8u) = 0
(-1 * 5u + 8u * 5u) = 0
(-5u + 40u2) = 0

Solving
-5u + 40u2 = 0

Solving for variable 'u'.

Factor out the Greatest Common Factor (GCF), '5u'.
5u(-1 + 8u) = 0

Ignore the factor 5.

Subproblem 1

Set the factor 'u' equal to zero and attempt to solve: Simplifying u = 0 Solving u = 0 Move all terms containing u to the left, all other terms to the right. Simplifying u = 0

Subproblem 2

Set the factor '(-1 + 8u)' equal to zero and attempt to solve: Simplifying -1 + 8u = 0 Solving -1 + 8u = 0 Move all terms containing u to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 8u = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 8u = 0 + 1 8u = 0 + 1 Combine like terms: 0 + 1 = 1 8u = 1 Divide each side by '8'. u = 0.125 Simplifying u = 0.125

Solution

u = {0, 0.125}

See similar equations:

| 4y=14-2x | | -1=-4+b | | (x^69-i^69)(x^69+i^69)=0 | | dy/dx=1/(2x-y^2) | | 7(x+2)=2x+57 | | 108=4z | | y=1/(2x-y^2) | | 0.5=1-e^-((t-1)/10) | | 4(4-a)-2(a-4)=-10-2a | | -2(5v-3)+3v=3(v+4) | | 7x+19+2x+15=133 | | -4h+6=-6h-8 | | 21b=14+b | | -17=m+71 | | 126=3p | | 1/3r-5=6 | | X*(x-5)=126 | | a+3b+5c=30000 | | 5r(r-7)=0 | | 3t-8=-7t | | 12x+1+10x=133 | | 2*x*y=48 | | 8/2H=8 | | 10-4x=11-x*3 | | 2q=-6q-8 | | 3x^3+37x-84=0 | | 10-4c=11-x*3 | | 2/3=x10 | | 1/7(-14r)= | | 7(v-5)-7=-4(-2v+8)-9v | | =25i^2+20i+25 | | -9+9m=10m-1 |

Equations solver categories